2015
DOI: 10.1152/jn.00560.2015
|View full text |Cite
|
Sign up to set email alerts
|

The functional asymmetry of ON and OFF channels in the perception of contrast

Abstract: -To fully understand the relationship between perception and single neural responses, one should take into consideration the early stages of sensory processing. Few studies, however, have directly examined the neural underpinning of visual perception in the lateral geniculate nucleus (LGN), only one synapse away from the retina. In this study we recorded from LGN parvocellular (P) ON-center and OFF-center neurons while monkeys either passively viewed or actively detected a full range of contrasts. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 105 publications
3
17
0
Order By: Relevance
“…This could enable more dots to be successfully matched up, increasing the number N of disparities which can be averaged on each side of the step-edge and so improving performance. They suggested that the independent processing of black and white dots could be mediated by the separate ON and OFF channels that are well-established early in the visual system (Jiang, Purushothaman, & Casagrande, 2015;Schiller, 2010;Schiller, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This could enable more dots to be successfully matched up, increasing the number N of disparities which can be averaged on each side of the step-edge and so improving performance. They suggested that the independent processing of black and white dots could be mediated by the separate ON and OFF channels that are well-established early in the visual system (Jiang, Purushothaman, & Casagrande, 2015;Schiller, 2010;Schiller, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported asymmetries between ON and OFF RGCs population in terms of transient or sustained response. Jiang et al (2015), analyzing retinal data from non-human primates, encountered OFF neurons having higher spontaneous activities, higher peak response amplitudes and with a more sustained temporal response compared to ON neurons. Nevertheless, we only observed asymmetries between central and peripheral RGCs, not particularly associated to ON or OFF populations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in primate retina emphasizes the differences in the electrophysiological response of a single RGC anatomical type (Midget) located in foveal, center and peripheral retina regions (Sinha et al, 2017; Masland, 2017), revealing different functional properties associated to a single RGC type. However, different functional properties for the entire RGC populations remain unknown together with the asymmetries present between ON and OFF cell population at different locations of the visual field (Chichilnisky and Kalmar, 2002; Zaghloul et al, 2003; Liang and Freed, 2010; Jiang et al, 2015; Leonhardt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…; Jiang et al. ). ON/OFF asymmetries also extend to neuronal spatial receptive fields and temporal properties (Dacey and Petersen ; Chichilnisky and Kalmar ; Pandarinath et al.…”
Section: Introductionmentioning
confidence: 98%
“…Intuitively, neurons in the ON and OFF pathways might be expected to respond similarly to stimuli of equal and opposite contrast. But in fact, the contrast response functions of ON and OFF neurons have systematic differences (Chichilnisky and Kalmar 2002;Zaghloul et al 2003;Liang and Freed 2010;Kremkow et al 2014;Jiang et al 2015). ON/OFF asymmetries also extend to neuronal spatial receptive fields and temporal properties (Dacey and Petersen 1992;Chichilnisky and Kalmar 2002;Pandarinath et al 2010;Ratliff et al 2010;Jin et al 2011;Nichols et al 2013).…”
Section: Introductionmentioning
confidence: 99%